In vitro evaluation of antimicrobial combinations against imipenem-resistant Acinetobacter baumannii of different MICs - Wan Zhu; Yang Wang; Wenxia Cao; Shiyue Cao; Jingping Zhang (Elsevier, 2018)
Background: This study was designed to verify the effectiveness of antimicrobial combination therapy against Acinetobacter baumannii isolates with different degrees of resistance to imipenem. Methods: A total of twenty-one isolates with imipenem MICs of 16 μg/ml (fifteen isolates) or 64 μg/ml (six isolates), as identified using the Vitek II system, were included in this study. The MICs of all the isolates to each drug were confirmed again using the broth microdilution method, and a checkerboard assay was used for the assessment of the in vitro effectiveness of various antibiotic combinations. Results: The results of susceptibility testing for single antibiotics indicated that imipenem-resistant Acinetobacter baumannii isolates exhibited good sensitivity to tigecycline and minocycline yet poor sensitivity to colistin, cefoperazone/sulbactam and levofloxacin. The distribution range of MICs for doripenem ranged from 0.5 μg/ml to 128 μg/ml, and the MICs ranged from 2 μg/ml to 32 μg/ml for levofloxacin. For combinations of imipenem and colistin, synergy was observed for the fourteen isolates with imipenem MICs of 16 μg/ml and one isolate with an imipenem MIC of 64 μg/ml. For the combinations of imipenem and cefoperazone/sulbactam, synergy was only observed for the fifteen isolates with imipenem MICs of 16 μg/ml. The combinations of imipenem and fosfomycin showed synergy for twelve isolates with imipenem MICs of 16 μg/ml. Other antimicrobial combinations based on colistin did not exhibit obvious synergy. Conclusion: The high sensitivity of tigecycline and minocycline in this study provides a reference for the clinical treatment of imipenem-resistant Acinetobacter baumannii infections in our region. The effectiveness of combination therapy may be predicted by the imipenem MICs of the isolates. The effect of fosfomycin in the combinations also reflects the clinical value of old drugs for new uses. These results suggest us that if we use carbapenem antibiotics in combination, more attention should be paid to the MICs of single drugs, and the economic costs should also be considered. Keywords: Imipenem-resistant Acinetobacter baumannii, Antimicrobial susceptibility, Checkerboard assay